The constitution of the academic field of education policy in Brazil: Historical aspects - Stremel, Silvana; Mainardes, Jefferson (Education Policy Analysis Archives, 2018)
This paper analyzes the constitution of the academic field of education policy in Brazil. The theoretical foundation is based on the contributions of Pierre Bourdieu’s theory on the notion of field. From the results of the analysis of the sources of the research, we present the historical aspects of the constitution of the academic field of education policy in Brazil divided into three moments, namely: 1) background of the academic field of education policy in Brazil (from 1820 to 1950); 2) institutionalization of the academic field of education policy (from the 1960s; and 3) expansion of the academic field of education policy (from the 1990s). We concluded that it is a comprehensive field and in permanent expansion and construction. Due to its nature, education policy does not constitute a monopoly of a scientific community, journals, research networks, etc., because it is something of public interest, and it can be discussed in different social and political spaces.